Analisis Cacat Pengecoran, Kekuatan Tarik, dan Kekerasan Logam Paduan AlSi Hasil Pengecoran Metode Sand Casting dengan Variasi Pengikat Lempung Lokal Bangkalan - Imam Muhtarom; Dwi Rahdiyanta (Diponegoro University, 2023)
This study aims to determine the casting defects, tensile strength, and hardness of the AlSi alloy obtained in the Sand Casting method with Bangkalan local clay as a binder. This experimental research uses the one-shot case study method in which a group of samples is given treatment. Furthermore, the research results were analyzed and described descriptively. This study uses three independent variables and three dependent variables. The independent variable is the local Bangkalan clay binder with varying percentages of 6%, 9%, and 12%, while the dependent variable is casting defects, tensile strength, and metal hardness. The research results show that the lowest casting defects are obtained on the AlSi metal surface, with a variation in the percentage of the binder of 12% with a total of 76 hole defects and 80-grain structure defects. At the same time, the highest tensile strength value is obtained in AlSi metal with a binder variation of 12% with a value of 11.188 kgf/mm². The highest hardness value is also obtained in AlSi metal, with a binder variation of 12% with a value of 131.9 HV. This study concludes that using local Bangkalan clay binder in 12% is the best sand mold binder variation compared to 6% and 9% binder variations.